2020
DOI: 10.37745/ejaafr/vol8.no4.pp89-111.2020
|View full text |Cite
|
Sign up to set email alerts
|

Responsibility Accounting and Corporate Investment Decisions among Listed Manufacturing Firms in Nigeria

Abstract: Over the years, corporate and institutional investors had suffered huge financial losses because of poor or wrong investment decisions taken based on manipulated financial information. Studies have shown globally that the practice of financial report misrepresentation commonly leads to loss of credibility, integrity and confidence in accounting information and the earnings become questionable. This situation now calls for additional sources of information that would enhance the quality of corporate investment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…We therefore accepted the alternate hypothesis that interest expense is significantly related to the sustainability growth of the banks in Nigeria. The finding seems agreeable with the findings of Adegbie, Urewa, and Owolabi (2020), Yisa, Ishola, and Folajimi (2020), who reported that the accountability account determines firm performance.…”
Section: H03: Interest Expense Has No Significant Relationship With S...supporting
confidence: 91%
See 3 more Smart Citations
“…We therefore accepted the alternate hypothesis that interest expense is significantly related to the sustainability growth of the banks in Nigeria. The finding seems agreeable with the findings of Adegbie, Urewa, and Owolabi (2020), Yisa, Ishola, and Folajimi (2020), who reported that the accountability account determines firm performance.…”
Section: H03: Interest Expense Has No Significant Relationship With S...supporting
confidence: 91%
“…Using t-test and Pearson's correlation, the results of the study showed that responsibility accounting has significant impact on performance. Yisa, Ishola, and Folajimi (2020) carried out a survey research designs with a population of 54 listed manufacturing firms in Nigeria. Using a targeted sampling technique, 510 respondents were selected from a sample frame of 34 firms; the study found that responsibility accounting had significant impact on companies' investment decision.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 2 more Smart Citations